1977
DOI: 10.1139/v77-473
|View full text |Cite
|
Sign up to set email alerts
|

13C and 33,34S isotope effects on the vapor pressure of liquid carbon disulfide

Abstract: GLBOR J A N C S~ and W. ALEXANDER VAN HOOK. Can. J. Chem. 55,3371 (1977). Prompted by the experimental investigation of Betts and Buchannon a thorough analysis of CS2 vapor pressure isotope effects has been made in the context of the theory of isotope effects in condensed phases and the available spectroscopic information. The agreement between the calculated and experimental results is satisfactory. The calculated results may be empirically described by the equations -0.529 In (PIICJIS2/PIJCJIS2) = + 0.00035 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In a study of 13 C/ 12 C vapor pressure isotope effects in carbon disulfide, Jancso and Van Hook [3] found that, when the usual procedure is followed of deducing the isotope effect on the zero-point energy Reprint requests to Prof. M. Wolfsberg, Department of Chemistry, University of California, Irvine, California 92717, USA.…”
Section: Background On Vapor Pressure Isotope Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 13 C/ 12 C vapor pressure isotope effects in carbon disulfide, Jancso and Van Hook [3] found that, when the usual procedure is followed of deducing the isotope effect on the zero-point energy Reprint requests to Prof. M. Wolfsberg, Department of Chemistry, University of California, Irvine, California 92717, USA.…”
Section: Background On Vapor Pressure Isotope Effectsmentioning
confidence: 99%
“…Thus, the observed spectroscopic fundamentals v max should be blue shifted by their respective dielectric shifts Av before the fundamentals are used for force constant calculations which in turn are used to calculate isotope effects on zeropoint energies in the condensed phase. This is just the procedure proposed by Jancsö and Van Hook [3]. Since dielectric shift values (Av L or zJv 0 ) are easily available for relatively few infrared absorptions.…”
Section: Unauthenticatedmentioning
confidence: 99%
See 1 more Smart Citation